Impact of the Tranexamic Acid on Bleeding Amount of Surgical Patient With Degenerative Spinal Disease: A Randomized Blinded Study - Yan, Lei; Yang, Huihong; Jiang, Haibin; Yu, Mingshan; Tan, Jie; Su, Tao; Xu, Guiping (Frontiers in Surgery, 2021)
Objective: To explore the effectiveness and safety of tranexamic acid (TXA) in reducing the bleeding amount of surgical patients with degenerative spinal disease in the perioperative period. Methods:A total of 80 cases of patients, who underwent elective posterior lumbar interbody fusion surgeries under general anesthesia, were enrolled in this study. The age of these patients ranged within 41-69 years old, and the surgical vertebral body segments were ≥2. The ASA classification was Level I or Level II. These patients were divided into two groups using the random number table (n=40):TXA group and control group (S group). In the TXA group, the skin was incised after the anesthesia induction, and 20 mg/kg of TXA was immediately injected into the vein. The injection continued at a rate of 10 mg·kg-1·h-1 during the surgery, until the surgery was finished. In the S group, IV and pump injection with an equal amount of normal saline (NS) were performed. Then, the RBC, Hb, HCT, AST, ALT, BUN, Cr, PT, TT, APTT, FIB and D-dimer were measured before the surgery and at one day after the surgery, and the SSFQ, intraoperative bleeding amount, homologous transfusion volume, rine volume, infusion quantity, surgical duration, drainage volume at 24 hours after the surgery, total bleeding amount and adverse event occurrence at one week after the surgery were recorded. Results:The RBC, Hb and HCT at one day after the surgery were higher in TXA group than in the S group (average P<0.05). Intraoperative bleeding, drainage volume at 24 hours after surgery, and total blood loss were lower in the TXA group than in the S group (average P<0.05). The SSFQ score and length of stay were lesser in the TXA group than in the S group (average P<0.05). The differences in AST,ALT,BUN,Cr,PT,TT,APTT,FIB and D-dimer at one day after the surgery for these two groups of patients had no statistical significance (average P>0.05). Conclusion: TXA can reduce the bleeding amount of surgical patients with degenerative spinal disease in the perioperative period and decrease the length of stay, but does not increase the occurrence rate of adverse events, thereby promoting postoperative rehabilitation.